Transcriptome-wide identification and expression analysis of the KT/HAK/KUP family in Salicornia europaea L. under varied NaCl and KCl treatments - Jia Wei; Richard John Tiika; Guangxin Cui; Yanjun Ma; Hongshan Yang; Huirong Duan (PeerJ, 2022)
Background The KT/HAK/KUP (KUP) transporters play important roles in potassium (K+) uptake and translocation, regulation of osmotic potential, salt tolerance, root morphogenesis and plant development. However, the KUP family has not been systematically studied in the typical halophyte Salicornia europaea L., and the specific expression patterns of SeKUPs under NaCl condition and K+ deficiency are unknown. Methods In this study, SeKUPs were screened from PacBio transcriptome data of Salicornia europaea L. using bioinformatics. The identification, phylogenetic analysis and prediction of conserved motifs of SeKUPs were extensively explored. Moreover, the expression levels of 24 selected SeKUPs were assayed by real-time quantitative polymerase chain reaction (RT-qPCR). Results In this study, a total of 24 putative SeKUPs were identified in S. europaea. Nineteen SeKUPs with the fixed domain EA[ML]FADL were used to construct the phylogenetic tree, and they were divided into four clusters (clusters I–IV). MEME analysis identified 10 motifs in S. europaea, and the motif analysis suggested that 19 of the identified SeKUPs had at least four K+ transporter motifs existed in all SeKUPs (with the exception of SeKUP-2). The RT-qPCR analysis showed that the expression levels of most SeKUPs were significantly up-regulated in S. europaea when they were exposed to K+ deficiency and high salinity, implying that these SeKUPs may play a key role in the absorption and transport of K+ and Na+ in S. europaea. Discussions Our results laid the foundation for revealing the salt tolerance mechanism of SeKUPs, and provided key candidate genes for further studies on the function of KUP family in S. europaea.